2014
DOI: 10.14507/epaa.v22n40.2014
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trends in Educational Decentralization in the United States and Developing Countries: A Periodization and Comparison in the Post-WWII Context

Abstract: In the present work, we fill a gap in the writing on the decentralization of educational governance by periodizing and comparing trends that have fallen under this label in both the United States and developing countries in the post-WWII period (1945-present). The findings are informed by a review of 127 decentralization-related studies from seven leading, peer-reviewed journals in comparative and international education, in addition to the Journal of Education Policy, Journal of Educational Administration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 179 publications
(95 reference statements)
0
31
0
2
Order By: Relevance
“…Conversely, in community control or local empowerment decentralization models, community groups make decisions for schools and are thus accountable to the community, not just boards of education or central office administration (Ornstein, 1983;Wohlstetter & McCurdy, 1991). Local empowerment models are more likely to occur when stakeholders outside of the district push to decentralize, while administrative decentralization tends to occur when those inside the district push for reform (Edwards & DeMatthews, 2014;Wohlstetter & McCurdy, 1991). Wissler and Ortiz (1988) also characterize school decentralization by the actors involved in the process.…”
Section: The Evolution Of School District Decentralizationmentioning
confidence: 99%
“…Conversely, in community control or local empowerment decentralization models, community groups make decisions for schools and are thus accountable to the community, not just boards of education or central office administration (Ornstein, 1983;Wohlstetter & McCurdy, 1991). Local empowerment models are more likely to occur when stakeholders outside of the district push to decentralize, while administrative decentralization tends to occur when those inside the district push for reform (Edwards & DeMatthews, 2014;Wohlstetter & McCurdy, 1991). Wissler and Ortiz (1988) also characterize school decentralization by the actors involved in the process.…”
Section: The Evolution Of School District Decentralizationmentioning
confidence: 99%
“…Accordingly, research on foundations' advocacy has so far primarily focused on large investors that are able to pursue their policy-making goals (Kornhaber, Barkauskas, & Griffith, 2016). Scholars have identified that such engagements lead to the promotion of particular policies such as school reforms like charter school expansion (Boyask, 2016;Edwards Jr. & DeMatthews, 2014;Scott, 2009;Woods, Woods, & Gunter, 2007) and teacher training such as Teach for All / Teach for America (Gautreaux & Delgado, 2016;LaLonde, Brewer, & Lubienski, 2015;Scott, Trujillo, & Rivera, 2016).…”
Section: Critical Theoretical and Empirical Perspectives On Philanthrmentioning
confidence: 99%
“…Educational reforms constantly affect the roles played not only by principals, teachers, administrators, and parents, but also by chairpersons of community organizations. Internationally, an observed shift in policy focus towards increased autonomy of schools through decentralization (simultaneously with introductions of national curricula and assessments) (Edwards Jr. & DeMatthews, 2014;Keddie, 2014;Lubienski, 2014) has drawn particular attention to school personnel and their roles in education. However, following the argumentation of Díaz-Gibson, Zaragoza, Daly, Mayayo, andRomaní (2017, p. 1040) such a reductionist approach "does not consider the interdependencies that exist between schools, districts, and the larger communities in which they reside."…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, los representantes del Banco Mundial que estaban trabajando en este programa, lo percibieron como una oportunidad aún más grande, tanto para hacerse de renombre, como para desarrollar una política que podría ser útil para su organización más adelante, a saber, una política que podría ser vendida como una buena práctica para otros países. En este punto, es necesario resaltar la tremenda popularidad de la descentralización como tema dentro de la industria del desarrollo internacional durante los años noventa (Edwards & DeMatthews, 2014), así como también la predominancia del Banco Mundial durante este tiempo con relación a otros organismos multilaterales, especialmente en el sector de la educación (Mundy, 1998).…”
Section: Estudios Educo: Una Visión Críticaunclassified
“…Es decir, mientras este tipo de estudios alrededor de EDUCO ha ofrecido la justificación para que los países experimenten con la descentralización a nivel de la comunidad, en la práctica, estos estudios han servido como una coraza política para introducir las políticas de descentralización que requieren, ya sea oficial o extraoficialmente, que los miembros de la comunidad: (a) realicen donaciones a la escuela, (b) ayuden con la construcción y reparación de la infraestructura de la escuela (edificios, letrinas, etc. ), (c) contribuyan a la administración de la escuela (por ejemplo, a través del monitoreo de los maestros y el director) y (d) participen en tareas administrativas o suplementarias (por ejemplo, el desarrollo de planes de mejoramiento en la escuela o la provisión de refrigerios para los estudiantes) (Edwards & DeMatthews, 2014).…”
Section: Implicaciones Internacionalesunclassified